Metagenomics reveals microbial community differences lead to differential nitrate production in anammox reactors with differing nitrogen loading rates. (1st February 2020) - Li, Wei; Zhuang, Jin-long; Zhou, Yuan-yuan; Meng, Fan-gang; Kang, Da; Zheng, Ping; Shapleigh, James P.; Liu, Yong-di
Abstract: Nitrate production during anammox can decrease total nitrogen removal efficiency, which will negatively impact its usefulness for the removal of nitrogen from waste streams. However, neither the performance characteristics nor physiological shifts associated with nitrate accumulation in anammox reactors under different nitrogen loading rates (NLRs) is well understood. Consequently, these parameters were studied in a lower NLR anammox reactor, termed R1, producing higher than expected levels of nitrate and compared with a higher NLR reactor, termed R2, showing no excess nitrate production. While both reactors showed high NH4 + -N removal efficiencies (>90%), the total nitrogen removal efficiency (<60%) was much lower in R1 due to higher nitrate production. Metagenomic analysis found that the number of reads derived from anammox bacteria were significantly higher in R2. Another notable trend in reads occurrence was the relatively higher levels of reads from genes predicted to be nitrite oxidoreductases ( nxr ) in R1. Binning yielded 27 high quality draft genomes from the two reactors. Analysis of bin occurrence found that R1 showing both a decrease in anammox bacteria and an unexpected increase in nxr . In-situ assays confirmed that R1 had higher rates of nitrite oxidation to nitrate and suggested that it was not solely due to obligate NOB, but other nxr -containing bacteria are important contributors as well. Our results demonstrate that nitrate accumulation can be a serious operational concern for the application of anammox technology to low-strength wastewater treatment and provide insight into the community changes leading to this outcome. Graphical abstract: Image 1 Highlights: Highlights: (max of 85 characters including spaces). NO3 − production was higher in mainstream anammox process. Abundance of nxr gene correlated with the high NO3 − production. High NO3 − likely due to activity of obligate NOB and other nxr -containing bacteria.